Phytochemicals analysis, Phenolic & flavonoids content of Cordia macleodii Hook leaves & Bark - O N Chaubey; Ravi Upadhyay; Niraj Kumar Tripathi; Amulya Ranjan (International Journal of Phytomedicine, 2015)
Cordia macleodii Hook (boraginaceae), a folklore medicinal plant, commonly known as "Shikari" in local language and found in Odisha and Madhya Pradesh. In this study, total phenolic content and concentration of flavonoids of two different extracts, from the ethanolic extract of Cordia macleodii (Boraginaceae) were determined using spectrophotometric methods. The total phenolic content ranged from 0.65±0.05 & 1.65±0.12 mg/g of dry weight of leaves & bark extract, expressed as gallic acid equivalents. The total flavonoids concentrations varied from 0.985±0.09 & 1.89±0.11 mg/g in bark & leaves extract, expressed as quercetin equivalents. Ethanolic extract of bark & leaves of Cordia macleodii showed the highest phenolic and flavonoids concentration repectively. The Cordia macleodii can be regarded as promising candidates for health management because of natural plant sources of phenolic and flavonoids with high value.